Transformasi Digital Pengelolaan Informasi Sekolah melalui Pemanfaatan Google Sites di MA Al Asror Patemon - Muljono Muljono; Imang Dapit Pamungkas; Nur Kholis Majid (Jurnal Pengabdian Masyarakat, 2026)
Digital transformation is an urgent need for educational institutions in improving the efficiency of information management and administrative transparency. However, there are still many schools that face limited human resource capacity and have not optimally utilized digital technology effectively. This community service activity aims to improve digital literacy and the efficiency of information management at MA Al Asror Patemon, Gunungpati District, Semarang City through the use of Google Sites. The methods used include socialization, technical training, technology application, mentoring, and continuous evaluation to ensure successful implementation. The results of the activity showed an increase in participants’ ability to manage school information digitally, the formation of a functional school website, and an increase in transparency and administrative efficiency, especially in the aspects of information management and financial documentation. In addition, this activity increases the accessibility of information for the public and stakeholders. This activity makes a real contribution to strengthening school governance, improving the digital competence of educators, and supporting the digital transformation of education in a sustainable and adaptive manner to technological developments.